EFEKTIFITAS Trichoderma sp DAN FUNGISIDA PROPINEB DALAM PENGENDALIAN PENYAKIT KARAT (Puccinia allii) PADA BAWANG DAUN DI DESA SINSINGON KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Fikka Caecillia Sajangbati; Berty H. Assa; Robert William Tairas (Universitas Sam Ratulangi, 2019)
ABSTRACTLeaf rust caused by Puccinia allii is one of the many diseases that attack onagricultural crops (horticultural crops). The existence of this disease can causevarious plant organs to become damaged, especially in leaf organs which are thetarget of a pandemic from the spread of the leaf rust disease. One of themicroorganisms that can be used to suppress plant diseases is Trichoderma spp. Thepurpose of this study was to determine the ability of Trichoderma sp and the use ofpropineb fungicide in controlling rust fungus on leeks in Sinsingon Village, PassiTimur District, Bolaang Mongondow Regency.This research was conducted at the Laboratory of the Indonesian Center forFood Crops and Horticulture Research (BPTPH) and then continued in SinsingonVillage, Passi Timur District, Bolaang Mongondow Regency. Field research wasarranged in a Randomized Block Design with 4 treatments that were repeated 6 times.The treatments were: A. Control, B. Trichoderma was applied to leaves, C.Trichoderma was applied to soil, D. Propineb fungicide. What was observed was thepercentage of attacks. Observations were made before being given treatment,treatment is done once a week after the first observation. The results showed (1)Microorganisms antagonist Trichoderma sp. effective in controlling P. allii leaf rustdisease.Keywords: leaf rust disease, Trichoderma sp, fungicide, leeks, P.allii.